Identifikasi Potensi Radioaktivitas pada Pisang Ambon (Musa Paradisiaca) dan Kulit Pisang Kepok (Musa Acuminata Balbisiana) Untuk Aplikasi Baterai Nuklir - rahastama, swastya; Hidayat, Jefri Pandu; Mahera, Adinda Kholif; Amelia, Rani Marizah; Salsabila, Syifa (SPECTA Journal of Technology, 2024)
Banana peel has a high potassium content, including the presence of the radioactive element K-40. As one of the beta emitters, K-40 has the potential to be a natural radioactive material for use as a betavoltaic nuclear battery source. In this study, the levels of K-40 content and radioactivity of kepok banana peel (Musa Acuminata Balbisiana) and ambon banana peel (Musa Paradisiaca), local varieties from the Balikpapan region, will be examined. Banana peel samples are first dried to reduce the water content and then processed into dry powder by heating for 20 hours. The mass and water content before and after the drying process are tested to observe shrinkage and its effects on the level of radioactivity. XRF testing is conducted to determine the potential potassium content of each sample. Radioactivity levels are measured using a Geiger Counter survey meter with sensitivity in the energy range of 50 KeV - 1.5 MeV. From the drying results, a greater decrease in mass is observed in kepok banana peel compared to ambon banana peel, accompanied by a significant reduction in water content. XRF test results indicate that the drying temperature has an effect on the emitted X-ray intensity. The activity content in kepok banana peel samples is found to be higher than in ambon banana peel. An estimated quantity of kepok and ambon banana peels needed to achieve the required 1 mCi activity for the nuclear battery is approximately 1.1 tons and 1.3 tons, respectively.